ON SHOOTING AND FINITE DIFFERENCE METHODS FOR NON-LINEAR TWO POINT BOUNDARY VALUE PROBLEMS - I. O., Ibrahim; S., Markus (International Journal of Research -GRANTHAALAYAH, 2018)
The paper investigates the efficacy of non-linear two point boundary value problems via shooting and finite difference methods. It was observed that the shooting method provides better result as when compared to the finite difference methods with dirichlet boundary conditions. It was observed that the accuracy of the shooting method is dependent upon the integrator adopted.